Changing trends: Beliefs and attitudes toward sharks and implications for conservation - Neves, Joao; McGinnis, Terran; Giger, Jean-Christophe (Ethnobiology and Conservation, 2022)
As history shows, and contrary to modern western society’s feelings, sharks were once respected and worshipped. Sensationalized media coverage negatively impacts the public’s perception of sharks and lack of information about management and conservation options negatively impacts policy makers’ ability to keep shark populations healthy. Understanding that people’s attitudes about sharks will influence their willingness to find a way to coexist with them, it is essential to acknowledge these attitudes when developing conservation measures. Just as risk management policies must adapt to new evidence-based information, so must shark conservation efforts adapt to the realities of public opinion. This perspective review, focused on the psychological aspects of human-shark interactions, highlights some of the current research, mostly from Australia and other countries where those interactions are more salient, on the beliefs and attitudes people have toward sharks. With this review, we hope to help policymakers and stakeholders, such as Environmental Non-Governmental Organizations (ENGOs) and the zoological community to better address some of the shark conservation challenges ahead.